Patient Safety Competence Among Diploma III Nursing Student In Jakarta, Indonesia; A Cross-Sectional Survey - Silvana Evi Linda; Tukimin; Nisha Nambiar (Holistic Nursing Plus, 2024)
Nursing students frequently made errors or near-misses due to non-compliance with patient safety protocols, including authenticating medication administration rights, verifying patient identification, and reviewing allergy status. This study was conducted using cross-sectional design at nursing Academy in Jakarta. The inclusion criteria were nursing diploma student at grade 3, nursing students who had not passed any patient safety training courses, those who passed the credit of “Fundamentals of Nursing and Management Patient Safety”, and those who started learning in the clinical setting. The Health Professional Education in Patient Safety Survey (H-PEPSS) was designed by Agency for Healthcare Research and Quality to evaluate recently students' levels of clinical safety. A descriptive statistic was used to analyze data using mean, standard deviation. A simple linear regression was done to determine the relationship between gender, age, and religion with patient safety competence. About 55% student have moderate level of competence, 28% good, and 20% excellent. There was no significant difference on patient safety competence among nursing students in 8 nursing colleges in Jakarta (p>0.05). Gender was associated contributed significantly to the variance in patient safety competence with R square was 28.8%. The study suggests nursing institutions should develop new approaches to improve patient safety competence and culture among students, preparing them for advanced technology education in healthcare institutions.